ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS PELAKSANAAN SISTEM PENGENDALIAN INTERNAL - Rosananda, Fairus La (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this paper is to determine what factors may affect the performance of accounting information systems on the effectiveness of the implementation of the internal control system. the company's internal control system greatly influences the performance of accounting information systems, because if the implementation of the control system is bad, then it will also be bad then the result. There are several factors that will affect the performance of the implementation of the accounting information system of internal control systems, such as 1) the factors involved in the development of the use of accounting information system itself, 2) the ability of technical personnel accounting information system, 3) the influence of the organization where he works and influence of political conditions and a global economic in which he resides 4) the support of the top management to motivate employees to work better and harder.Keyword : Accounting Information System and Internal Control System